Membangun Generasi Cerdas dan Berkarakter Yang Kompeten Serta Pendewasaan Diri Sebagai Seorang Mahasiswa Perguruan Tinggi - Ahmad Faizal; Edy Soesanto; Mohamad Aren Gracia Shandy (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Higher education plays an important role in creating quality human resources in the future. As university students, our main task is not only to achieve academic achievements, but also to form strong, competent characters and be ready to face global challenges. Building a generation that is intelligent, characterized and competent as well as a process of self-maturation is an important step to prepare individuals who excel in science with integrity, leadership and good social skills. The intelligent generation has knowledge and skills according to the times, while the generation with character is able to integrate moral values, ethics and empathy in everyday life. In the context of higher education, this process is not only related to the formal curriculum, but also non-academic experiences that play a role in the personal growth of each student. The process of self-maturation in higher education trains students to be more independent, critical, and have a broad outlook on life and be responsive to various social problems. The formation of balanced character and competence will prepare students to contribute optimally in various aspects of life, including in the world of work, society and as responsible citizens. Therefore, it is important for every student to understand the essence of this process and commit to continuing to develop, both academically and personally, so that they can become a generation that is not only intellectually intelligent, but also has noble values ​​that can benefit the nation. and the world. Thus, higher education should not only focus on achieving academic degrees alone, but also on efforts to develop students who are mature in thinking, acting and character, so that they are able to face an increasingly complex and challenging world.